2019
DOI: 10.4172/2161-1122.1000530
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Radiation Protection Protocols amongst Students of a Dental College

Abstract: Objective: To assess the knowledge, attitude and practice of radiation protection among dental students in a dental college in eastern India. Background: Radiation hazard is one of the major challenges of modern dental practices. Reliance on radiation imaging has increased tremendously during recent years. The effect of radiation on human being is very negative. Knowledge and awareness regarding radiation protection during dental training is crucial for ensuring better radiation protection practice after train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Whereas Srivastava et al ., 83.3%, Rathi Rela reported 56%, Swapna et al ., reported 59%, Almohaimede et al ., reported 60.8%, and Basheer et al ., reported 63.5% of their participants were knew that dental X-rays are harmful to health. [ 15 17 18 19 20 ] Our results show that the range of knowledge better than the previous studies. Even though the dental radiation dose is minimal, its better to avoid taking radiographs in the first trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 41%
“…Whereas Srivastava et al ., 83.3%, Rathi Rela reported 56%, Swapna et al ., reported 59%, Almohaimede et al ., reported 60.8%, and Basheer et al ., reported 63.5% of their participants were knew that dental X-rays are harmful to health. [ 15 17 18 19 20 ] Our results show that the range of knowledge better than the previous studies. Even though the dental radiation dose is minimal, its better to avoid taking radiographs in the first trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 41%
“…Study conducted by Rathi Rela et al on the topic named Knowledge, Attitude and Practice of Radiation Protection Protocols amongst Students of a Dental College, has the conclusion on the negative side. 12 Similar study was conducted by Agrawal B et al on the topic named Evaluation of Radiation Protection Awareness amongst General Dental Practitioners of Western Rajasthan in India where the author advised to conduct continuing education programs on the radiation protection aspect. 13 In another study by Sumona Pal et al got the result as the protective measures were not satisfactory and they reinforced the use of ALARA principle.…”
Section: Limitationmentioning
confidence: 75%
“…This is In a previous study conducted by Swapna In the present study, the majority of the study population (58%) reported that dental radiography is absolutely contraindicated in pregnant women. Previous study conducted by Swapna et al [15] reported 42% of the study population, Rela et al [2] reported that 64% of study population and Rela et al [16] reported that 46% of the study population assume that it is an absolute contraindication for pregnant patients to be radiographed. This is almost similar to our study.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, most of the study participants (65%) agreed that the ideal distance of operator (Position Distance Rule) when exposed to dental radiation is 6feet, 90°-135°. Rela et al [16] reported that 52% of the study population agreed that ideal position distance rule and Amal et al [15] reported that 72.3% of the study population agreed the ideal distance of the operator when exposed to dental radiation is 6 feet and 90°-135°.…”
Section: Resultsmentioning
confidence: 99%